Debt sustainability analysis and its policy implications for Ukraine - Tetiana Bogdan (Public and Municipal Finance)
Since the outbreak of the russian invasion in 2022, Ukraine’s public debt has risen sharply, and debt sustainability turned out to be a matter of concern. This study aims to conduct a comprehensive debt sustainability analysis (DSA) for Ukraine, focusing on probabilistic judgments about the trajectory of public debt, the government’s gross financing needs in the 2025–2028 period, and essential policy measures to prevent an unsustainable debt situation. The DSA incorporates references to quantitative debt-related benchmarks and assessments of performing a debt treatment and changing the structure of budget deficit financing. Four medium-term scenarios are run: a baseline scenario, a negative scenario, a positive macro-scenario, and a policy shock scenario. The first three scenarios yield public debt stocks from 94.8% to 128.8% of GDP in 2028, above the intermediate threshold of 82% and far above the final threshold of 65%. Even under the baseline projections, public debt trajectory and gross financing needs magnitudes deviate considerably from the benchmark levels. Only the policy shock scenario is compatible with ensuring public debt sustainability, being conditional on a substantial extension of foreign grants, and applying a significant haircut through the second debt restructuring. The results suggest that avoiding public debt crisis while meeting recovery and reconstruction needs would require raising the share of grants up to around 45% in the structure of foreign official financing and debt reduction by at least 50% in the framework of new foreign debt restructuring, covering official bilateral debt and euro-bonds’ debt. Acknowledgment This study is published as an output of the EURIZON project “Ukraine’s Foreign Financing Needs and the EU’s Role in Restoring External Sustainability and Long-Term Growth of the Ukrainian Economy,” which is funded by the European Union’s Horizon 2020 Research and Innovation Programme under grant agreement No. 871072.